A gay Nigerian man's journey to asylum in the USA. Issue 4 (5th April 2019) - Nguyen, Mytien; Handoko, Ryan; Asabor, Emmanuella; McKenzie, Katherine C
Abstract : We report the case of an individual from Nigeria seeking asylum in the USA on the basis of persecution for being gay, who was physically and sexually assaulted in Nigeria and detained upon arrival to the USA. We present physical examination findings and the results of a brief mental health evaluation performed at Elizabeth Detention Center in New Jersey for his asylum evaluation. Individuals are able to seek asylum as members of a "particular social group", in this case, being gay. They seek asylum in the USA as they will continue to be at risk for harm if they stay in their home countries. However, the detention of asylum seekers often violates US human rights obligations and can occur without formal oversight. We explore the unique complications and experiences of lesbian, gay, bisexual, transgender and queer asylum seekers throughout the asylum process, from Nigeria to a detention centre in the USA.